ANALISIS PERBANDINGAN ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) PADA PERUSAHAAN SEBELUM DAN SESUDAH MERGER MAUPUN AKUISISI PERIODE TAHUN 2010 - 2012 (Perusahaan Publik yang Terdaftar di Bursa Efek Indonesia) - KUSUMA WARDANI, IKA (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this study was to determine and analyze the differences before and after the merger or acquisition on the public company listed in Indonesia Stock Exchange which has been expansion by way of merger and acquisition. Researchers used a period of 3 years before and 3 years after the company merged and acquired. This research is a comparative research with quantitative methods. The sample in this study using purposive sampling method amounted to 14 companies of the population of 24 companies, with data collection in the form of documentation in the form of the announcement of the merger and acquisition, and annual financial statements. Data analysis techniques used in this research is to test for normality using the Kolmogorov-Smirnov Test and statistical difference test by using non-parametric Marginal Homogeneity Test using SPSS tool 19.0. The results of this study indicate that there were no significant differences in Economic Value Added (EVA) values before and after mergers or acquisitions and there are significant differences in Market Value Added (MVA) values before and after mergers or acquisitions. . Keywords: economic value added (EVA), market value added (MVA), merger and acquisition